The role of telecommunications operators on smart home service platforms - Hannes Kuebel; Ruediger Zarnekow (International Telecommunications Society (ITS), 2014)
The formation and evolution of digital service platforms is changing the balance of powers in the ICT industry. In particular, telecommunications operators feel the need to gain more control over the creation and provision of new services and to revise their roles in different service ecosystems. Therefore, both researchers and practitioners call for a better understanding of emerging digital services, such as smart home services, and corresponding platform strategies. Therefore, we assess the roles of leading telecommunications operators on smart home service platforms based on data gathered from in-depth desk research. Drawing on platform theory and the industry perspective on the smart home market, we identify how operators control technological and organizational assets to act as system integrator, enabler, broker and neutral platforms. Further, we discuss operators' strategies and major challenges in establishing common service platforms in a varied smart home ecosystem. Additionally, we point out aspects of interest for further research.
Keywords: 330; smart home; service platforms; business strategy; telecommunications industry